Upaya Meningkatkan Keaktifan dan Hasil Belajar Matematika Siswa melalui Pembelajaran Student Team Achievement Divisions - Okta Hidayanti; Benedictus Kusmanto; Esti Harini (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to describe the process of applying the Student Team Achievement Divisions (STAD) cooperative learning model as an effort to improve the activeness and learning outcomes of students in class VIII B, SMP N 3 Banguntapan. This type of research is Classroom Action Research which consists of two cycles, each of which consists of 4 stages, namely (1) planning, (2) action, (3) observation, and (4) reflection. The subjects of this study were students of class VIII B, SMP N 3 Banguntapan, with a total of 30 students. Data collection techniques used were observation techniques, documentation techniques, and test techniques. The results showed an increase in each indicator of student activity. In the first cycle, the value of the percentage of student activity 57.916% increased in the second cycle to 79.578%. While the average student mathematics learning outcomes increased from 44.83 in the pre cycle to 70.6 in the first cycle then the second cycle increased to 79.4.